PENGARUH PERLAKUAN PENDAHULUAN BIJI KEMIRI TERHADAP RENDEMEN DAN SIFAT MINYAKNYA (Pretreatment effects of candle nut seedoil on oil yiled and its properties) - Bambang Wiyono; Poedji Hastoeti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The purpose of this research is to study the pretreatment effects of candle nut seed oil on oil yield and its properties. Pretreatments consisted of dry-frying steaming and unpretreatment. The dry-frying was carried out at 100°C for 15 minutes, and steaming was carried out for 30 minutes at the same temperature. Each pretreatment was pressed at 110 kg/cm2 and the difference between means were tested with the LSD procedure.The results showed that pretreatment gave a highly significant effect on oil yield, specific gravity, saponification number and unsaponifiable matter. It also provided a significant effect on acid number and acid content caloulated as oleic acid. The dry-frying produced the highest of oil yield, a higher specific gravity, and a lower acid number, acid content and unsaponifiable matter based on the oil yield, specific gravity and acid number, the dry-frying method is the best pretreatment compared to the others.